Evaluation of the Effectiveness of Virtual Teaching Assistant in Online Collaborative Learning - Erdogan, Aylin; Kara, Sevda; Y?lmaz, Hale (Al-Hijr: Journal of Adulearn World, 2024)
The rise of online learning has introduced various tools and technologies aimed at enhancing the learning experience, with virtual teaching assistants (VTAs) being one of the most prominent innovations. VTAs can support both students and instructors by providing real-time feedback, answering questions, and facilitating collaboration in online environments. However, the effectiveness of VTAs in fostering successful online collaborative learning experiences remains underexplored. This study evaluates the effectiveness of VTAs in online collaborative learning environments, focusing on their impact on student engagement, collaboration, and academic performance. A mixed-methods research design was employed, combining quantitative data from student performance assessments with qualitative feedback from surveys and interviews. The study involved 200 students across multiple online courses that integrated a VTA to support collaborative activities. Data was collected over the course of a semester. The results indicate that the use of VTAs significantly enhanced student engagement and collaboration, leading to improved academic performance. Students in the experimental group showed a 15% increase in collaboration scores and a 20% improvement in academic performance compared to the control group. This study concludes that VTAs can play a crucial role in improving the effectiveness of online collaborative learning by fostering greater student interaction, providing timely support, and enhancing learning outcomes.